Circadian rhythm and exercise - Shibata, S.; Tahara, Y. (The Journal of Physical Fitness and Sports Medicine, 2014)
In mammals, the circadian clock organizes physiological processes, including sleep/wake patterns, hormonal secretion, and metabolism, and regulates athletic performance. The circadian system is responsive to environmental changes such as light/dark cycles, food intake, and exercise. In this review, we will focus on the central and peripheral circadian molecular clock system, discussing how circadian rhythm affects athletic performance and muscle metabolism, and how exercise entrains the circadian rhythm. Importance of exercise training in rescuing circadian deficit-induced metabolic disorder is also discussed. The interaction of the circadian clock and exercise, called "chrono-exercise," is poised to become an important research field of chronobiology.